Editorial PPP 15(1) - Medeiros Marinho dos Santos, Larissa; Saraiva de Queiroz, Isabela; Rodrigues de Alvarenga Filho, José; de Fatima Aranha de Queiroz e Melo, Maria (Revista Pesquisas e Práticas Psicossociais, 2020)
-